2011
DOI: 10.1016/j.pain.2011.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Links between nurses’ organisational work environment and upper limb musculoskeletal symptoms: Independently of effort–reward imbalance! The ORSOSA study

Abstract: The role of psychosocial factors in the development of upper limb musculoskeletal disorders has now been clearly demonstrated. However, only a few studies have analysed the association between the organisational work environment and musculoskeletal disorders in health care workers. The main goal of this study was to test the hypothesis that some specific organisational constraints may be related to upper limb musculoskeletal symptoms experienced by registered nurses, independently of the effort/reward imbalanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 55 publications
0
20
0
9
Order By: Relevance
“…Five studies examined populations in care facilities [21,23,25,26,39] and four studies researched the association between ERI and musculoskeletal pain in employees of passenger transport companies [27-29,36], although the study by Dragano et al [28] was a reanalysis of Joksimovic et al [27]. This study was still included because – unlike the paper by Joksimovic et al – it considered chronification of musculoskeletal pain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies examined populations in care facilities [21,23,25,26,39] and four studies researched the association between ERI and musculoskeletal pain in employees of passenger transport companies [27-29,36], although the study by Dragano et al [28] was a reanalysis of Joksimovic et al [27]. This study was still included because – unlike the paper by Joksimovic et al – it considered chronification of musculoskeletal pain.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the psychosocial factors ascertained using the ERI model, ten studies [25-27,30-33,36,37,39] analysed other psychosocial factors. These were based on the demand-control model [10], the Copenhagen Psychosocial Questionnaire (COPSOQ) [41] and the Nursing Work Index – Extended Organisation Questionnaire (NWI-EO Questionnaire) [42].…”
Section: Resultsmentioning
confidence: 99%
“…For example, Sakata et al 3) reported that 12.2 and 44.4% of medical resi- dents in Japan experienced effort/reward imbalance and overcommitment, whereas Conway et al 8) reported that 16.1 and 26.3% of health-care workers in Italy experienced effort/reward imbalance and overcommitment. A survey of a group of nurses in the ORSOSA study in France identified effort/reward imbalance in 10.7% of the nurses and overcommitment in 40.8% of the nurses 19) . Comparisons of the results of the current study with earlier studies of other occupations in Taiwan show effort/reward ratios of 0.74 (0.22) and 0.97 (0.34) in litigious lawyers and healthy engineers, respectively 2,20) .…”
Section: Discussionmentioning
confidence: 99%
“…Among healthcare workers, few studies looked at the association between MSD and the organizational characteristics of the work environment, mainly focusing on shiftwork (7,11). More recently, studies have addressed the effect of the perception of healthcare workers of the work-unitlevel psychosocial and organizational environment on the occurrence of MSD (12,13), including MSD of the neck and shoulders (14). However, these studies were crosssectional and no conclusion could be drawn concerning causal relationships.…”
Section: Lamy Et Almentioning
confidence: 99%